Embedding organizations : societal analysis of actors, organizations, and socio-economic context - Maurice, Marc; Sorge, Arndt (Advances in organization studies, 2000)
The widely discussed 'globalization' of economic activities has given rise to a renewed interest in the relations between such tendencies, the nature and demarcation of societies, and the nature and strategies of various actors and organizations within and cross-cutting societies. One approach to capture and express these themes has been Societal Analysis, initially developed above all to confront the internationally comparative study of work, organization, education and training, industrial relations, business and industrial structures. After twenty-five years of practising and developing Soci.